STUDY ON THE DENSIFICATION OF ALN-TIB2 COMPOSITES BY HOT PRESSED SINTERING - Li , Ming (Управління розвитком складних систем, 2021)
The AlN-TiB2 composites were prepared by hot pressing sintering process and the effects of TiB2 content and sintering process on the densification of AlN-TiB2 composites were studied. The results showed that at 1900℃ for 1h, the relative density reached more than 98.6% and the TiB2 content had no effect on densification of the composites. The phase composition and microstructure of the composites were also studied. Two-phase BN and TiN are newly formed in the sintering process of AlN-TiB2 multiphase material, so the multiphase material is composed of four phases, the primary crystal phase is AlN and TiB2, and the secondary crystal phase is BN and TiN. With the increase of sintering temperature and the extension of holding time, the density of AlN-TiB2 multiphase materials gradually increases. The optimum sintering temperature and holding time were 1900℃ and 1h respectively. The addition of TiB2 does not affect the sintering of multiphase materials.The multiphase materials have achieved high density.